2021
DOI: 10.3390/e23010085
|View full text |Cite
|
Sign up to set email alerts
|

Transport Efficiency of Continuous-Time Quantum Walks on Graphs

Abstract: Continuous-time quantum walk describes the propagation of a quantum particle (or an excitation) evolving continuously in time on a graph. As such, it provides a natural framework for modeling transport processes, e.g., in light-harvesting systems. In particular, the transport properties strongly depend on the initial state and specific features of the graph under investigation. In this paper, we address the role of graph topology, and investigate the transport properties of graphs with different regularity, sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 62 publications
0
15
2
Order By: Relevance
“…This is motivated by the often asked question whether the efficiency of transportand its noise dependence on graphs -are correlated with the network structure described, e.g., by connectivity, regularity and various centrality measures. Studies in the perfect state transfer context indicate that network connectivity measures are not good indicators of the fidelity of state transfer [56][57][58]. However, although we calculated a large number of centrality measures and 3 different clustering coefficients for the networks we study in the current paper, we could not find any statistically significant relation with the efficiency.…”
Section: Classification Of Transport Efficiencycontrasting
confidence: 64%
“…This is motivated by the often asked question whether the efficiency of transportand its noise dependence on graphs -are correlated with the network structure described, e.g., by connectivity, regularity and various centrality measures. Studies in the perfect state transfer context indicate that network connectivity measures are not good indicators of the fidelity of state transfer [56][57][58]. However, although we calculated a large number of centrality measures and 3 different clustering coefficients for the networks we study in the current paper, we could not find any statistically significant relation with the efficiency.…”
Section: Classification Of Transport Efficiencycontrasting
confidence: 64%
“…Konno [4,5] proved a weak limit theorem for the CTQW on the line and trees, and showed that there is a striking contrast to the central limit theorem of symmetric classical random walks. Mülken and Blumen [6] reviewed applications of CTQWs to transport in various systems, and recently Razzoli et al [7] analytically determined subspaces of states having maximum transport efficiency for many graph topologies. Benedetti et al [8] described CTQW on dynamical percolation graphs with the goal of analyzing the effect of noise produced by randomly adding or removing graph edges.…”
Section: Introductionmentioning
confidence: 99%
“…For an initially localized state or a superposition of two vertex states evolving under the transport Hamiltonian (4) it is unlikely to achieve a high transport efficiency. In additin, the transport efficiency η usually decreases with the order N of graph [56]. Our starting point is the observation that breaking the symmetries of the graph can actually improve the transport efficiency.…”
Section: Minimal Perturbation Approachmentioning
confidence: 99%